If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2x = 5 + -4x Solving 3 + -2x = 5 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 3 + -2x + 4x = 5 + -4x + 4x Combine like terms: -2x + 4x = 2x 3 + 2x = 5 + -4x + 4x Combine like terms: -4x + 4x = 0 3 + 2x = 5 + 0 3 + 2x = 5 Add '-3' to each side of the equation. 3 + -3 + 2x = 5 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 5 + -3 2x = 5 + -3 Combine like terms: 5 + -3 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| ln^2(x)=4x | | B=-3x+9y-5y+5x-4x+6y | | 12=4x+6 | | L=-9c+4b-8b+6c-3c+6b | | 9y-5=0 | | 10+2(2x-1)=16 | | (ln^2x)=4x | | (lnx^2)=4x | | 2x^2-60x=2x^2 | | W=-5c+3c-9+4 | | z+3(2-i)=5+i | | S=-5b-3b+6-7 | | x^2+x+2.5=0 | | D=-9c+6c-8c | | 64/x=4 | | A=-7y+6y | | 0.50x+0.25(30)=21.5 | | 50+(6x-2)=180 | | B=-9x-3x | | -14(2x-10)=28 | | 4a-3=15 | | 5x+5=8x-9 | | -5p+5+6p=10 | | Ep+q=29 | | f(x+3)=x^2+5x+3 | | M=-4x+9z-9+2x-2z+4 | | 2(x-5)=3(5x+1) | | 9x-4=52-5x | | x^4-3x^3+4x+1=0 | | B=6x+3a-9+7x-8a+2 | | 4x-7+9x+13-5x-4= | | 6*x+x=63 |